'We Are All Kin': Reconsidering Labour and Class in Calgary, 1919 - Bright, David (Labour/Le Travailleur, 1992)
Recent labour historiography on the strike wave of 1919 has debated whether events are better explained within a framework of western exceptionalism (that is,stressing regional factors) or of a national revolt (that is stressing class tensions). A study of Calgary suggests that neither of these interpretations is fully satisfactory. Calgary workers, by 1919, certainly displayed a class identity and a class consciousness, but these were tempered by broader cultural bonds and by continuing entrepreneurial aspirations. Despite a generation of economic disillusionment, characterized by falling real wages and the high frequency of unemployment, labour continued to place faith in craft unions, political reforms, and class co-operation. Fitting neither of the established interpretation frameworks, the experience ofworkers in Calgary, 1919, indicates the need for a reassessment of current conceptions of class relations.